2010
DOI: 10.1152/japplphysiol.00462.2010
|View full text |Cite
|
Sign up to set email alerts
|

Group III and IV muscle afferents contribute to ventilatory and cardiovascular response to rhythmic exercise in humans

Abstract: We investigated the role of somatosensory feedback on cardioventilatory responses to rhythmic exercise in five men. In a double-blind, placebo-controlled design, subjects performed the same leg cycling exercise (50/100/150/325 ± 19 W, 3 min each) under placebo conditions (interspinous saline, L(3)-L(4)) and with lumbar intrathecal fentanyl impairing central projection of spinal opioid receptor-sensitive muscle afferents. Quadriceps strength was similar before and after fentanyl administration. To evaluate whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

30
413
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 331 publications
(446 citation statements)
references
References 73 publications
30
413
3
Order By: Relevance
“…In younger individuals, the pulmonary capillary recruitment probably occurs with greater efficiency, allowing an expansion of the so-called West zone III to the region of zones I and II, maintaining a more appropriate V/Q ratio 33 . It should be noted that the increased ventilation in exercise is not only related to the CO2 concentration, but also with afferent stimuli from the mechanoreceptors 34,35 . Evidence of that is data from Araujo and Monteiro 36 indicating that there are substantial differences in the VE and also in VE/VO2, with probably different afferent stimuli, when an individual walks or runs for the same velocity on the treadmill.…”
Section: Discussionmentioning
confidence: 99%
“…In younger individuals, the pulmonary capillary recruitment probably occurs with greater efficiency, allowing an expansion of the so-called West zone III to the region of zones I and II, maintaining a more appropriate V/Q ratio 33 . It should be noted that the increased ventilation in exercise is not only related to the CO2 concentration, but also with afferent stimuli from the mechanoreceptors 34,35 . Evidence of that is data from Araujo and Monteiro 36 indicating that there are substantial differences in the VE and also in VE/VO2, with probably different afferent stimuli, when an individual walks or runs for the same velocity on the treadmill.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, although hyperventilation during heavy exercise is related to perception of effort, it may be an event independent of the traditional model of 'central command' that drives breathing via parallel activation of motor and respiratory centers. Thus, these recent studies [44][45][46][47][48]54,55) collectively emphasize the importance of a cognitive process such as perception of effort in respiratory regulation during heavy exercise. However, the formation mechanism of effort sense during heavy exercise and the role of effort sense in ventilatory control are still not clear 61) .…”
Section: Role Of the Perception Of Effort In Ventilatory Regulation Dmentioning
confidence: 96%
“…For instance, an essential role for muscle afferent feedback in respiratory regulation has been suggested by the observation that blocking somatosensory feedback by fentanyl injection caused hypoventilation during a cycling time trial 44) . Furthermore, using a similar pharmacological method, Amann et al 45) demonstrated that blocking somatosensory feedback substantially attenuated the ventilatory and also perceptual responses to heavy exercise. These findings by Amann et al 44,45) raise the possibility that input of groups III and IV muscle afferents contributes to the central motor command driving respiration during exercise 46) .…”
Section: Role Of the Perception Of Effort In Ventilatory Regulation Dmentioning
confidence: 99%
See 1 more Smart Citation
“…TO THE EDITOR: In their recent paper, Amann and colleagues (1) report an experiment in which they used a powerful analgesic, fentanyl, to block afferent feedback from Group III and IV neurons innervating the locomotor muscles. The authors investigated the effects of this experimental treatment on various physiological and perceptual responses to cycling exercise at different power outputs.…”
mentioning
confidence: 99%